Evaluation of school sports development policy towards improving the quality of education - Permatasari, Nabella Intan; Haq, Mohammad Syahidul; Hazin, Mufarrihul; Hariyati, Nunuk; Purwoko, Budi (Pendidikan Jasmani, Kesehatan, dan Rekreasi Universitas Nahdlatul Ulama Sunan Giri, 2025)
This study aims to evaluate the policy of sports development in senior high school (SMAN) Surabaya and assess its contribution to improving the quality of Education. The research method uses a quantitative approach with CIPP evaluation model (Context, Input, Process, Product). Data collection through closed questionnaires, semi-structured interviews, and direct observation of 40 respondents from various high schools in Surabaya. Data analysis using multiple linear regression test . The results showed that although the sports program has been running regularly and have a positive impact on the formation of student character, its implementation is still hampered by limited means and funds. Evaluation and monitoring have also not been systematically organized. Linear regression showed that the results of the analysis showed that the understanding of policy (③=0.40, p = 0.002), sports facilities (③=0.20, p = 0.05), and the implementation of activities (③=0.35, p = 0.01) significantly affect the quality of Education.Conclusion Sports Development Policy in SMAN Surabaya is generally positive and has a significant impact on character building and improving student discipline. Further research suggests that schools and policy makers should improve sports facilities and strengthen the allocation of special funds for sports development so that programs can run more optimally.